1997
DOI: 10.1006/cogp.1997.0671
|View full text |Cite
|
Sign up to set email alerts
|

The Possible-Word Constraint in the Segmentation of Continuous Speech

Abstract: We propose that word recognition in continuous speech is subject to constraints on what may constitute a viable word of the language. This Possible-Word Constraint (PWC) reduces activation of candidate words if their recognition would imply word status for adjacent input which coultl not be a word -for instance, a single consonant. In two word-spotting experiments, listeners found it much harder to detect apple, for example, in fapple (where [f] alone would be an impossible word), than in vujfapple (where vuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
281
3
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(318 citation statements)
references
References 64 publications
30
281
3
4
Order By: Relevance
“…We may therefore find that listeners are less able to Syntactic Predictability 9 make use of predictive syntactic information when the words that carry it are acoustically reduced because listeners may not have enough time to recover from the reduction of the auxiliary verb before hearing the participle. The idea that the importance of some linguistic cues depends on the availability of other cues is part of both accounts and is consistent with Mattys et al's (2005) and Norris et al's (1997) frameworks on cue integration in speech segmentation.…”
Section: Introductionsupporting
confidence: 71%
“…We may therefore find that listeners are less able to Syntactic Predictability 9 make use of predictive syntactic information when the words that carry it are acoustically reduced because listeners may not have enough time to recover from the reduction of the auxiliary verb before hearing the participle. The idea that the importance of some linguistic cues depends on the availability of other cues is part of both accounts and is consistent with Mattys et al's (2005) and Norris et al's (1997) frameworks on cue integration in speech segmentation.…”
Section: Introductionsupporting
confidence: 71%
“…The finding of a target position effect is not specific to our study (Banel & Bacri, 1995;McQueen, 1998;McQueen et al, 1994;Norris, McQueen, Cutler, & Butterfield, 1997;van der Lugt, 2001). Assuming that target identification takes about the same time in both embedding positions, the RT difference suggests that for initial embedding, other processes take place after listeners have identified the target.…”
Section: Discussioncontrasting
confidence: 53%
“…Although Norris et al (1997) found that adult segmentation was constrained by the PWC regardless of whether target words occurred at the end of the longer nonsense item (apple in ''fapple'' or ''vuffapple'') or at the beginning (sea in ''seash'' or ''seashub''), the response time advantage of possible over impossible contexts which they observed was largest for words in final position, with the context preceding the word. Studies of adult listening with other techniques have also shown greater inhibition of activation for finalembedded words preceded by impossible contexts than for initial-embedded words followed by impossible contexts (Vroomen & de Gelder, 1997).…”
Section: Resultsmentioning
confidence: 80%
“…Further research on adult word recognition has attempted to account for how everyday listeners successfully deal with unknown lexical items and rule out implausible segmentations of utterances containing such items. Norris, McQueen, Cutler, and Butterfield (1997) proposed that online segmentation and recognition of words is guided by a bias against considering any segmentation that leaves a single consonant as a residue.…”
Section: Introductionmentioning
confidence: 99%